A synthesis of luminescence and 14C dated dust mass accumulation rates for loess-palaeosol sequences from the Middle Danube Basin - Perić, Zoran ; 0000-0003-0116-8895; Radaković, Milica G.; Marković, Rastko S.; Marković, Slobodan B. (Boreas, 2025)
The Middle Danube (Carpathian) Basin is considered to encompass some of the thickest and most complete records of aeolian dust deposition in Europe, covering the last two glacial–interglacial cycles. In this study, independent, published chronologies based on absolute dating methods were compiled for 34 loess-palaeosol sequences and modelled using Bayesian statistics. Mass accumulation rates (MARs) calculated from the Bayesian age models range from 50 to 1922 g m−2 a−1 with a mean value of 317±35 g m−2 a−1. The glacial–interglacial changes of the MAR estimates only partially agree with the accepted dust deposition model, where high accumulation rates are observed during the cold glacial stages, while low values are typical for the warmer interglacial periods. There is a rapid increase of MAR values during Marine Isotope Stage (MIS) 2, with the highest deposition in most cases observed ~25–18 ka. During MIS 3, the dust deposition was 1.8 times higher than during MIS 4. Regionally, the MARs appear to be highest in the northern part of the Middle Danube Basin, showing decreasing values towards the south. However, due to a variety of factors such as low dating resolution, age distribution, and biases in the dating method, it is debatable whether these results are representative estimates of atmospheric dust activity in the Middle Danube Basin during MIS 5–MIS 1.